Opioid use and dropout in patients receiving oral naltrexone with or without single administration of injection naltrexone. (1st February 2015) - Sullivan, Maria A.; Bisaga, Adam; Glass, Andrew; Mishlen, Kaitlyn; Pavlicova, Martina; Carpenter, Kenneth M.; Mariani, John J.; Levin, Frances R.; Nunes, Edward V.
Highlights: Low-severity opioid users achieved retention of 60% at 6 months in behavioral naltrexone therapy (BNT) + oral naltrexone with a single administration of injection naltrexone (XR-NTX). High-severity opioid users experienced high early attrition in BNT-XR-NTX as a result of increased withdrawal discomfort from oral naltrexone combined with XR-NTX. When patients are transitioned from XR-NTX, oral naltrexone should be phased in slowly. Abstract: Background: Adherence to oral naltrexone has been poor and can be improved somewhat with behavioral therapy. We compared behavioral naltrexone therapy (BNT) to compliance enhancement (CE) and tested efficacy of single-dose injection naltrexone (XR-NTX; 384 mg) with behavioral therapies at further improving adherence to oral naltrexone. Methods: A 24-week, randomized, placebo-controlled trial ( n = 125) compared four treatment conditions following inpatient detoxification and oral naltrexone induction: (1) BNT + XR-NTX; (2) BNT + placebo injection; (3) CE + XR-NTX; and (4) CE + placebo injection. All participants were maintained on oral naltrexone throughout the trial. Primary outcome was retention in treatment. Results: Of 89 randomized participants, 78.7% (70/89) completed 4 weeks, 58.2% (54/89) completed 8 weeks, 47.2% (42/89) completed 12 weeks, and 25.8% (23/89) completed 24 weeks. A Cox proportional hazards regression modeled time to dropout as a function of treatment condition, baseline opioid dependence severity (bags per day of heroin use), and their interaction. Interaction of conditions by baseline severity was significant ( X 3 2 = 9.19, p = 0.027). For low-severity patients (≤6 bags/day), retention was highest in the BNT − XR-NTX group (60% at 6 months), as hypothesized. For high-severity (>6 bags/day) patients, BNT − XR-NTX did not perform as well, due to high early attrition. Conclusion: For low-severity heroin users, single-dose XR-NTX improved long-term treatment retention when combined with behavioral therapy. In higher-severity opioid-dependent patients, XR-NTX was less helpful, perhaps because, combined with oral naltrexone, it produced higher blood levels and more withdrawal discomfort. When cost considerations recommend oral naltrexone following XR-NTX, the latter should be phased in slowly.